Legal Consequences of the Transfer of Undivided Joint Property on the Validity of the Deed Made by the Land Deed Official (PPAT) - Putri Safira; Darmawan; Novi Sriwahyuni (Genesis Law and Social Sciences, 2025)
This study analyses the legal consequences of the transfer of undivided marital property on the validity of a sale and purchase deed made by a Land Deed Official (PPAT). The research focuses on the legal implications arising when one party in a marriage transfers joint property without the consent of the other spouse. Using a normative and empirical juridical approach, this paper examines statutory provisions, legal doctrines, and judicial precedents, including the Decision of the Banda Aceh Sharia Court No. 185/Pdt.G/2021/MS.Bna. The findings reveal that any transfer of joint property conducted without mutual consent violates Article 36 of Law No. 1 of 1974 on Marriage and Article 92 of the Compilation of Islamic Law (KHI), rendering the resulting PPAT deed legally invalid and void by law. Moreover, the PPAT may be held civilly, administratively, and ethically responsible for negligence in verifying the legal status of the property. This study highlights the importance of legal certainty and professional accountability in land registration and transfer processes to protect the rights of all parties involved.